”Meneeks tunteisiin?” : sähköisen palautteen herättämä tunne ja toiminta, oppilaan näkökulmasta - Lappalainen, Pauliina (2024)
The purpose of the study was to investigate the emotions experienced by young people in the final year of comprehensive school during lessons, and particularly the kinds of feelings aroused in students by electronically provided lesson feedback. The study also examined how feedback has influenced actions and learning in school from the perspective of emotion, and how feedback could be better utilized to support learning and motivation. During the interviews and data analysis, actions were examined in general across all lessons and specifically in physical education lessons, aiming to identify whether feedback provided in physical education differs from feedback in other subjects.